Respon Pemberian Dosis Pupuk Kandang Kambing terhadap Produksi Bayam Merah (Aternatera Amoena Voss) dan Kandungan C-Organik Tersedia Tanah di Dusun Brai Kecamatan Alok Timur Kabupaten Sikka - Yovita Yasintha Bolly; Oktaviana Rosario Sere Gili (Agriculture - Jurnal Ilmu Pertanian, 2023)
This study aims to investigate the effect of goat manure fertilizer on the production of red spinach (Alternanthera amoena Voss) and soil organic carbon (C-organic) content in Brai Hamlet, Alok Timur District, Sikka Regency. The research was conducted from November to December 2022 using a randomized complete block design (RCBD) with five fertilizer dose treatments (control, 6 kg, 12 kg, 18 kg, and 24 kg per bed) and four replications. The results showed that the highest fertilizer dose (24 kg/bed) produced the highest yield of red spinach, reaching 3.88 kg per bed, while the control only produced 1.40 kg per bed. The application of goat manure fertilizer significantly affected plant growth and yield but did not show a significant effect on increasing soil C-organic content. Laboratory analysis indicated that the final soil C-organic content was classified as high to very high, but no significant changes were detected statistically. In conclusion, goat manure fertilizer effectively increases the yield of red spinach, but it has not yet significantly improved soil C-organic content within the research period.